Human-to-monkey transfer learning identifies the frontal white matter as a key determinant for predicting monkey brain age - He, Sheng; Guan, Yi; Cheng, Chia Hsin; Moore, Tara L.; Luebke, Jennifer I.; Killiany, Ronald J.; Rosene, Douglas L.; Koo, Bang-Bon; Ou, Yangming (Frontiers in Aging Neuroscience, 2023)
The application of artificial intelligence (AI) to summarize a whole-brain magnetic resonance image (MRI) into an effective "brain age" metric can provide a holistic, individualized, and objective view of how the brain interacts with various factors (e.g. genetics, lifestyle) during aging. Brain age predictions using deep learning (DL) have been widely used to quantify the developmental status of human brains, but their wider application to serve biomedical purposes is under criticism for requiring large samples and complicated interpretability. Animal models, i.e. rhesus monkeys, have offered a unique lens to understand the human brain -being a species in which aging patterns are similar, but for which environmental and lifestyle factors are more readily controlled. However, applying DL methods in animal models suffers from data insufficiency as the availability of animal brain MRIs is limited, compared to many thousands of human MRIs. We showed that transfer learning can mitigate the sample size problem, where transferring the pre-trained AI models from 8,859 human brain MRIs improved monkey brain age estimation accuracy and stability. The highest accuracy and stability occurred when transferring the 3D ResNet (mean absolute error (MAE)=1.83 years) and the 2D Global-local Transformer (MAE=1.92 years) models. Our models identified the frontal white matter as the most important feature for monkey brain age predictions, which is consistent with previous histological findings. This first DL-based, anatomically interpretable, and adaptive brain age estimator could broaden the application of AI techniques to various animal or disease samples and widen opportunities for research in non-human primate brains across the lifespan.